Literature, Criticism and Publishing Industry in "De Mar a Mar" (1942-1943): a Reading in the Light of Publishing Networks of Galician Exile in Argentina - Gerhardt, Federico (Madrygal. Revista de Estudios Gallegos, 2017)
This article analyzes the relationships between literature, criticism and the publishing market in the literary magazine De Mar a Mar, published in Buenos Aires between 1942 and 1943 by a group of exiles from the Spanish Civil War, mostly, descendents of Galician. The analysis focuses on two particular aspects of the magazine: on the one hand, in relation to its content, the paper examines the bibliographical news and the editorial advertising; on the other hand, in relation to its context, it is considered the work of its directors and regular collaborators in the book publishing industry in Argentina, which is in its “golden age”. The linking of these two aspects analyzed sheds light in respect of the editorial connections that underlie De Mar a Mar and that influence in the composition of the successive issues of the magazine.